Compact Ka-Band lens antennas for LEO satellites - Costa, J. R.; Fernandes, C. A.; Godi, G.; Sauleau, R.; Le Coq, L.; Legay, H. (IEEE Transactions on Antennas and Propagation, 2008)
This paper presents and compares two new compact lens antenna configurations for data link communications with LEO satellites at 26 GHz. These lenses match a secant type radiation pattern template in the elevation plane while having a mechanically scanned sector beam in azimuth to enhance gain as much as possible. No rotary joints or multiple feeds are required and emphasis is put also on the compactness of the proposed solutions (< 6 lambda). Two alternative lens configurations are evaluated numerically and experimentally: one is based on modified axial-symmetric dome lens geometry, and the other one consists of a full 3-D double-shell lens antenna. In contrast to current nearly omnidirectionnal antennas, the directivity of our lens prototypes is above 15.4 dBi. Up to 4.2 dB loss obtained in the prototypes can be significantly reduced by using lower loss dielectrics and matching layers, without affecting the conclusions. The numerical and experimental results are in good agreement with the radiation specifications given the compact size of the antennas.